Project A1a: On designing and implementing benefit-sharing mechanisms : - Mulligan, Mark; Rubiano Mejía, Jorge Eliécer (2009)
This is about identifying which benefit-sharing and coordination mechanisms work best under which circumstances for basins anywhere in the Andes and the reasons underpinning failure or success in specific basin instances. It is about providing a common platform - a negotiation support system - as a means of informing the BSM negotiation process with the best available knowledge. The project will seek to identify the variables that need to be taken into account when BSM are designed and proposed as ways to curb rural poverty and environmental degradation. The possible effects of global change on these variables will be analyzed, along with the likelihood that changes in these variables will impact the viability of BSM. Adaptations to BSM that may help them accommodate global change will be explored.